Materiais arqueológicos da Cividade de Bagunte presentes no Museu de História Natural e da Ciência da Universidade do Porto - Almeida, Carlos A Brochado de; Almeida, Pedro Brochado de; Morais, Rui; Filipe, Ana Rita (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2020)
The Cividade of Bagunte is a big fortified settlement from the Iron Age Period, which was widely transformed during the Romanization process of the Northwest of the Iberian Peninsula. The urban reorganization of the town happened in the 2nd half of the first century, with the Flavian dynasty. It had several archaeological campaigns during the 19th, 20th and 21th centuries. If the archaeological material dug in recent campaigns is in storage, the vast majority of the material collected in the 20th century isn´t accounted for, exception made for the Torques made of silver. As for the archaeological artefacts gathered in the 19th century, al are store at the University of Porto – Faculty of Sciences, being the subject of this article.